Evaluation of state-run STI/RTI clinics in the state of Haryana, India through a supportive supervision approach - Rama S Rath; Mahender Singh; S A Rizwan; Ayush Lohiya; Giridara Gopal; Vijay Silan (Indian Dermatology Online Journal, 2014)
Introduction: Sexually transmitted infections (STIs) are an important public health problem because of their adverse effects on reproductive health of men and women. About 5% of adult population in India suffers from STIs. To tackle this issue the government has set up reproductive tract infection (RTI) clinics across the country. Aims: To assess the effect of supportive supervision on the quality of services provided in STI/RTI clinics in the state of Haryana, India. Settings and Design: Selected state-run STI/RTI clinics, facility-based pre- and post evaluation study. Material and Methods: Sixteen STI/RTI clinics were selected for the study, including six from government facilities and 10 from targeted intervention sites across five districts of Haryana. From each of the selected sites one physician in-charge was interviewed twice with an interval of 2-3 months using pretested formats. Scores were given in selected domains of STI/RTI management for each visit and the improvement was assessed. Statistical Analysis: Wilcoxon signed rank test. Results: A total of 16 physicians one from each site were interviewed. Improvement in mean score of the physicians for knowledge about STI/RTI was 3.6 points. Similarly for skills score, which measured the physicians′ skill in various domains of running STI/RTI clinics, the mean improvement was 3.1 points. Both the improvements were statistically significant (P < 0.001). Conclusions: Supportive supervision proved to be a useful tool for monitoring and improving the quality of services provided by the STI/RTI clinics.